2003
DOI: 10.2135/cropsci2003.1367
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Leaf‐Blade Nitrogen and Relative Seedcotton Yields

Abstract: ceed plant needs or when fertilizer applications are not synchronized with plant uptake. Today, methods for Nitrogen fertilization is a required production practice for cotton predicting N status of cotton grown in the Midsouth are (Gossypium hirsutum L.) with risks arising from under-and overeither inaccurate or require additional studies before fertilization. Tissue testing for diagnosing N deficiencies in crops can use leaf blades and the total N concentration, but this practice has the critical values used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 13 publications
(18 reference statements)
3
23
4
Order By: Relevance
“…The linear and quadratic increase of leaf N concentration as N rate increased (Table 3) is consistent with the plant partitioning N to the younger leaves (upper main stem leaves) and reproductive parts when N is not limited (Tewolde et al, 2005). As dry matter accumulation increased (1st square to mid-bloom), N is partitioned to reproductive structures, which would decrease leaf N concentrations in the younger leaves (Bell et al, 2003;Tewolde et al, 2005). However, the reported critical leaf N concentration measured at mid-bloom for the Southeast Cotton Belt is 41 g kg −1 (Bell et al, 2003).…”
Section: Applied Nitrogensupporting
confidence: 78%
See 1 more Smart Citation
“…The linear and quadratic increase of leaf N concentration as N rate increased (Table 3) is consistent with the plant partitioning N to the younger leaves (upper main stem leaves) and reproductive parts when N is not limited (Tewolde et al, 2005). As dry matter accumulation increased (1st square to mid-bloom), N is partitioned to reproductive structures, which would decrease leaf N concentrations in the younger leaves (Bell et al, 2003;Tewolde et al, 2005). However, the reported critical leaf N concentration measured at mid-bloom for the Southeast Cotton Belt is 41 g kg −1 (Bell et al, 2003).…”
Section: Applied Nitrogensupporting
confidence: 78%
“…As dry matter accumulation increased (1st square to mid-bloom), N is partitioned to reproductive structures, which would decrease leaf N concentrations in the younger leaves (Bell et al, 2003;Tewolde et al, 2005). However, the reported critical leaf N concentration measured at mid-bloom for the Southeast Cotton Belt is 41 g kg −1 (Bell et al, 2003). No leaf N concentrations measured at mid-bloom were above this reported critical level for any growing season.…”
Section: Applied Nitrogenmentioning
confidence: 92%
“…Authors emphasized that increasing plant height for narrow-row-space cotton is not desirable because it interferes with harvest. Furthermore, high N rates lead the plants into continuous growth, lengthening the cycle and reducing yield (Bell et al, 2003). Other studies found similar results of N rates leading to taller plants (Bogiani et al, 2011;Gottardo, 2012;Galhardo et al, 2013).…”
Section: Yield Parametersmentioning
confidence: 65%
“…Higher rates of N may be required in narrow row spacing due to higher populations compared to conventional systems. Nevertheless, excessive use of N can reduce yield because plants will grow taller and take longer to mature (Bell et al, 2003), which is not desired in narrow-row systems. Hence, N rates must be appropriate for avoiding excessive growth in a long cycle.…”
Section: Introductionmentioning
confidence: 99%
“…The sensitivity of cotton leaf N to N application is greater at early bloom than at any other growth and developmental stages [12] [13]. This trend indicates monitoring of leaf N nutrition status at early bloom is especially helpful in deciding whether supplemental N application is required.…”
Section: Effects Of In-season Side-dress N Applications On Leaf N Conmentioning
confidence: 99%